Evidence for association of an ACCN1 gene variant with response to lithium treatment in Sardinian patients with bipolar disorder. (November 2011) - Squassina, Alessio; Manchia, Mirko; Borg, Joseph; Congiu, Donatella; Costa, Marta; Georgitsi, Marianthi; Chillotti, Caterina; Ardau, Raffaella; Mitropoulos, Konstantinos; Severino, Giovanni; Del Zompo, Maria; Patrinos, George P
Aims: Bipolar disorder (BD) is a lifelong psychiatric illness characterized by manic and depressive episodes affecting 1–5% of the general population. Among mood-stabilizing treatments, lithium represents the mainstay in the therapeutic management of BD. However, besides the relatively high rate of excellent responders, a significant fraction of patients present patterns of partial or nonresponse to lithium. This variability might be influenced by genetic factors, even though findings have so far been inconclusive. Here, we present the results of an exploratory genome-wide scan followed by extended genotyping carried out on a sample of 204 Sardinian BD patients characterized for lithium response.Materials & methods: Phenotypic assessment of lithium response was made using the retrospective criteria of long-term treatment response scale. Using Affymetrix ® 6.0 SNP arrays, we genotyped a subsample of 52 BD patients evenly distributed at the extreme ends of the treatment response scale. The associated SNPs were then prioritized and selected for validation and extended genotyping in the whole sample of BD patients characterized for lithium response. Association was also tested using the scale for a quantitative trait analysis.Results: Our findings showed that several SNPs were nominally associated (p ≤ 10 -5 ) with lithium response in the subgroup of 52 BD subjects. Some association signals were then confirmed in the extended sample. The strongest association, also supported by the quantitative trait analysis, was shown for a SNP located in intron 1 of the ACCN1 gene, encoding for a cation channel with high affinity for sodium and permeable to lithium.Conclusion: Our results indicate that ACCN1 gene is a potential candidate for response to lithium treatment that would serve as a genetic marker of lithium efficacy for BD patients. Original submitted 13 May 2011; Revision submitted 12 July 2011